Kontribusi Dukungan Sosial Keluarga Terhadap Stres Akademik Siswa SMAN 1 Palopo - Ririn Angreni; Muhammad Irham Zainuri; Marhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the contribution of family social support to the academic stress of Palopo 1 Public High School students. The research used quantitative methods with simple random sampling techniques, involving 165 class XI students as samples from a total population of 428 students. Data was collected through an online questionnaire which was processed using the SPSS 25 application. Validity and reliability tests showed that the instruments used were valid and reliable. The results of multiple linear regression analysis show that family social support has a significant negative effect on students' academic stress, while resilience has a significant positive effect. The regression model was able to explain 12% of the variation in academic stress, indicating that other factors also influence students' academic stress.